The AN ANALYSIS OF STRATEGIC MANAGEMENT'S IMPACT ON BUSINESS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
To deal with the current economic crisis, many firms have had to learn how to transform their ideas into action. As a result,solid strategic planning can help organisations withstand the unstable business climate in various respects. Many studies have looked at how small and medium-sized businesses in India have improved their transaction volumes, customer counts, market shares, and profits by implementing strategic management approaches. Questionnaires were administered to 120 small business owners in Lagos State, India, who volunteered their answers. Descriptive statistics and regression analysis were used to examine the data. SME growth in customer base and market share may be attributed in large part to their competitive advantages and business strategy. The results, on the other hand, show that the structure of an organisation has a small but favourable impact on the transaction volumes of small and medium-sized businesses.